Sosialisasi Kesadaran Keamanan Digital di Era Revolusi Industri 4.0 - Pertiwi, Novia Ayu Sekar; Umardiyah, Fitri; Mansyur, Muhammad Naufal; Munir, Misbahul; Sapi’i, Imam; Sholichah, Amanathus; Fudlah, Tisa Nailatu (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Dukuhdimoro Village, Mojoagung, Jombang, is the location of community service activities focusing on the socialization of digital security in the era of the Fourth Industrial Revolution. Through the Service Learning approach, this program aims to raise awareness among the community about cybercrime threats and how to protect themselves in the use of information technology. Involving various stakeholders such as students, youth from religious organizations, and village residents, the program provides information about digital crime risks and preventive measures that can be taken. Program evaluation indicates a significant increase in participants' understanding of digital crime and high learning interest among the community. Through the publication of the